Analisis Pengaruh Kompensasi, Motivasi dan Komitmen Affective terhadap Kinerja Karyawan (Studi Empiris di PT Nagamas Surya Kencana Tegal) - Diantoro; Syariefful Ikhwan; Akbar Nuur PDW; Ari Kristiana; Khalid Iskandar (Program Studi Manajemen Universitas Muhadi Setiabudi, 2019)
This research was conducted to determine the effect of compensation, motivation, and organizational commitment on the performance of employees of PT Nagamas Surya Kencana Tegal. This research was conducted during August 2017. Data collection was carried out using a questionnaire that had been tested for validity and reliability by measuring a 5-point Likert scale. The sample in this study were employees of PT Nagamas Surya Kencana Tegal with 50 respondents. Hypothesis testing is done by multiple regression analysis using the SPSS. The results of this study indicate that partially compensation has a positive and significant effect on employee performance; obtained t count> t table (2.466> 1.678) and has a significance value of 0.018 (0.018 <0.05). Motivation has a positive and significant effect on employee performance; by obtaining the value of t count> t table (2.915> 1.678) and has a significance value of 0.013 (0.006 <0.05). Affective commitment has a positive and significant effect on employee performance; obtained t count> t table (2.126> 1.678) and has a significance value of 0.039 (0.039 <0.05). And compensation, motivation, and organizational commitment simultaneously have a positive and significant effect on employee performance by obtaining f count> f table (33.409> 3.20), and have a significance value of 0.000 (0.000 <0.05).